Canine antibody response to Lutzomyia longipalpis saliva in endemic area of visceral leishmaniasis. - Batista, Luís Fábio Da Silva; Matta, Vânia Lúcia Ribeiro Da; Tomokane, Thaise Yumie; Pacheco, Acácio Duarte; Silveira, Fernando Tobias; Rossi, Claudio Nazaretian; Marcondes, Mary; Laurenti, Márcia Dalastra (Sociedade Brasileira de Medicina Tropical - SBMT, 2016)
Abstract:INTRODUCTION: Canine exposure to Lutzomyia longipalpis bites and the potential of Leishmania infantum transmissibility for the vector were evaluated.METHODSImmunoglobulin G (IgG) anti-Lu longipalpis saliva and -L. infantum, and blood parasite load were determined in dogs from endemic areas of visceral leishmaniasis.RESULTSBlood parasitism was similar between symptomatic and asymptomatic dogs. IgG anti-L. infantum was higher in symptomatic dogs, but IgG anti-Lu. longipalpis saliva was mostly observed in higher titers in asymptomatic dogs, indicating vector preference for feeding on asymptomatic dogs.CONCLUSIONSOur data suggest a pivotal role of asymptomatic dogs in L. infantum transmission in endemic areas.
Keywords: Canine leishmaniasis; Anti-Lutzomyia longipalpis saliva antibody; Transmissibility